2022
DOI: 10.1098/rstb.2021.0364
|View full text |Cite
|
Sign up to set email alerts
|

Social concepts and the cerebellum: behavioural and functional connectivity signatures in cerebellar ataxic patients

Abstract: Neurocognitive research on social concepts underscores their reliance on fronto-temporo-limbic regions mediating broad socio-cognitive skills. Yet, the field has neglected another structure increasingly implicated in social cognition: the cerebellum. The present exploratory study examines this link combining a novel naturalistic text paradigm, a relevant atrophy model and functional magnetic resonance imaging. Fifteen cerebellar ataxia (CA) patients with focal cerebellar atrophy and 29 matched controls listene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 108 publications
1
4
0
Order By: Relevance
“…These results align with situated views of language disruptions, which posit that specific cognitive and socio-affective deficits are reflected in germane linguistic categories [ 69 , 70 ]. Specifically, disruption of neurocognitive systems mediating self-awareness and perspective taking would lead to reduced self-reference, leading to exocentric (third person) linguistic references to construe daily events.…”
Section: Discussionsupporting
confidence: 83%
“…These results align with situated views of language disruptions, which posit that specific cognitive and socio-affective deficits are reflected in germane linguistic categories [ 69 , 70 ]. Specifically, disruption of neurocognitive systems mediating self-awareness and perspective taking would lead to reduced self-reference, leading to exocentric (third person) linguistic references to construe daily events.…”
Section: Discussionsupporting
confidence: 83%
“…Lopes da Cunha et al [ 60 ] use a novel paradigm in which they combine a novel naturalistic text-reading paradigm, a relevant atrophy model, and functional magnetic resonance imaging (fMRI) to investigate the comprehension of social and non-social texts in patients with cerebellar ataxia (CA) and controls. They found that CA patients were impaired in grasping social but not non-social concepts.…”
Section: Overview Of This Theme Issuementioning
confidence: 99%
“…Other papers focus more explicitly on language and its relationship with concepts, showing the importance of inner language, verbal labels and word associations for concrete and abstract concepts, and highlighting the role of language in enhancing cognition. Across the various sections, the theme issue offers many insights into the differences between kinds of concepts, from the significant distinction between concrete and abstract ones [ 2 , 8 , 9 , 56 , 57 ], to specific concepts like the religious [ 58 ], the social [ 59 , 60 ], the olfactory [ 61 ] and the emotional ones [ 38 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, reciprocal links between linguistic and socio-cognitive skills have been reported in varied populations. For example, comprehension of social concepts correlates with the integrity of social cognition networks in neurodegenerative patients (Birba et al, 2022 ; Lopes da Cunha et al, 2023 ), and emotional language can bias moral judgments in laypersons but not in legal experts (Baez et al, 2020 ). Our study adds to this trend, showing that socio-affective functions may also be shaped by individual language profiles.…”
Section: Discussionmentioning
confidence: 99%